2012
DOI: 10.1002/smll.201200465
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cell Adhesion and Neurite Outgrowth by Patterned Gold Nanoparticles with Tunable Attractive or Repulsive Surface Properties

Abstract: Guiding of neuronal cells on surfaces is required for the investigation of fundamental aspects of neurobiology, for tissue engineering, and for numerous bioelectronic applications. A modular method to establish nanostructured chemical templates for local deposition of gold nanoparticles is presented. A process comprising nanoimprint lithography, silanization, lift-off, and gold nanoparticle immobilization is used to fabricate the particle patterns. The chemical composition of the surface can be modified by in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 59 publications
(65 reference statements)
1
35
0
Order By: Relevance
“…Various potential applications of micro‐ and nanoscale structured surfaces have been proposed, which include tissue engineering, medical implant with blood compatibility, cancer cell detection, and electrophysiological devices . In particular, implementation of topographic surfaces into neural interface was introduced as a promising approach to regulate cell functions in vitro and improve performance of electrophysiological devices . Size and periodicity of the topography need to be carefully selected, as the cell responses are significantly influenced by the structures with dimensions from micro‐ to nanoscale by different mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Various potential applications of micro‐ and nanoscale structured surfaces have been proposed, which include tissue engineering, medical implant with blood compatibility, cancer cell detection, and electrophysiological devices . In particular, implementation of topographic surfaces into neural interface was introduced as a promising approach to regulate cell functions in vitro and improve performance of electrophysiological devices . Size and periodicity of the topography need to be carefully selected, as the cell responses are significantly influenced by the structures with dimensions from micro‐ to nanoscale by different mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…PC12 cells were used as the neuronal differentiation model. It has been proposed that different charged coating materials play a critical role in cell attachment, which further lead to different effects on cell differentiation. Different charges also modulate neurite outgrowth process by influencing calcium ions channel .…”
mentioning
confidence: 99%
“…The AuNPs surface was further functionalized with positively charged ligands to generate cell attractive surfaces for neuritis growth. Cell experiment showed that neurites growth and spreading on the AuNPs patterns with healthy morphology . Additionally, Hammond et al demonstrated the different patterning approach based on polymer on polymer stamping (POPS).…”
Section: Self‐assembled Monolayers Of Nanomaterials As Biomaterialsmentioning
confidence: 99%